SOSIALISASI PROGRAM JAMINAN KESEHATAN NASIONAL OLEH TIM BADAN PENYELENGGARA JAMINAN SOSIAL KEPADA PASIEN DI RSUD RAA SOEWONDO KABUPATEN PATI - Rika Rejeki; Septo Pawelas Arso; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2014)
BPJS  is a law-based health insurance provider in Indonesia formed based on Constitution Number 40/2004 and Constitution Number 24/2011. The purpose of the socialization is to educate people about the JKN program. The result of the early survey is that 8 of the 10 patients are known to have not understood the JKN program. This research is intended to describe the socialization of JKN program by BPJS team to patients in RSUD RAA Soewondo Pati, while the research subjects are the main informants and triangulation informants. The methods of data collecting of the research are deep interview and documentation, while data analysis consists of data transcript, data reduction, data serving, and deduction. The result of this research indicates that : material presented on socialization is about benefits, membership requirements, and registration groove, there have not been specified human resources for socialization of JKN program, the fund and facilities needs for the socialization of JKN program have been covered by RSUD RAA Soewondo Pati that room, banners, posters, and leaflets, socialization methods consists of enlightening and face to face education, planning process, consists of human resources for conducting socialization, facilities, audience determining, strategy and methods making, and the material that will be conveyed, coordination of BPJS team in the form of meeting, while coordination between BPJS Kesehatan and BPJS team in the form of meeting and intensive communication by phone, patients knowledge’s are known to have increased after socialization of JKN program. The recommendations of this research are adding of and training for workers of JKN program, repair of room in ticket hole, redesigning of and material adding to leaflet, planning strategy and methods improvement and resources requirement, and BPJS team coordination improvement.